Multidisciplinary Laser Facility Driven by New-Generation High-Repetition Laser - Gonçalo Vaz; Joana Alves; Victor Hariton; Celso P. João; João Marques; David Cristino; Hugo Gomes; Cara Priebe; Petr Pokorny; Maria P. Santos; Hugo Pires; Gonçalo Figueira (Photonics)
For many years, high-power laser technology has been divided between industrial applications, which prioritize higher average powers and repetition rates, and academic research, which focuses on achieving higher peak powers and ultrashort pulse durations. The introduction of Yb-doped crystals in laser technology has paved the way for a new generation of laser sources that bridge the gap between industrial and academic requirements, combining high average power with ultrashort pulse capabilities. These advancements enable the integration of compact, adaptable front-end stages, making such lasers versatile for scientific applications. In Lisbon, the Laboratory of Intense Lasers leverages this technology with a system that combines commercial and custom-built front-end stages to enhance operational flexibility. In this paper, we present the current status of this facility and outline upcoming upgrades. We also showcase applications enabled by these high-power laser sources, including semiconductor studies, bi-photonics, and time-resolved spectroscopy.